Association between tumor characteristics and second primary cancers with cutaneous melanoma survival: a nationwide cohort study - Zheng, Guoqiao; Chattopadhyay, Subhayan; Sundquist, Kristina; Sundquist, Jan; Försti, Asta; Hemminki, Akseli; Hemminki, Kari (Pigment cell & melanoma research, 2020)
The increased survival in malignant cutaneous melanoma (melanoma) is probably due to early diagnosis combined with improved treatment most recently. National health campaigns and screening programs for melanoma detection were started in Sweden several decades ago. We want to assess the influence of tumor characteristics, based on the TNM classification, and of second primary cancers on overall survival in melanoma. We used the Swedish Cancer Registry to assess all-cause survival in melanoma from 2003 to 2015. Hazard ratios (HRs) were estimated using multivariable Cox regression models. A total of 19,773 melanoma patients were diagnosed with TNM data. Survival showed a strong improving trend over time (p-trend <.001). T1a was the most common classification (48.0% of all), while higher T class was associated systematically with worse survival (p-trend <.001). For distant metastases, the HR was 3.17, accounting for 0.9% of the patients. Any types of second primary cancers, other than melanoma, were associated with an HR of 2.00, accounted for 6.7% of all cases. Even if melanoma survival in Sweden ranks among the best national rates, the large percentage of patients with advanced tumors (T3b, T4a, and T4b, 17%) and 21% of deaths with T1a call for improved preventive and follow-up strategies.
Gesehen am 17.02.2021